Al-Ghazali's Thought of Islamic Education And its Relevance with the Modern Education - Arifin, Zainul (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2018)
The Islamic world has many scientists who have brilliant concepts and thoughts in various disciplines. Their concepts and thoughts have contributed to the success of various scientific disciplines both for the Islamic and Western world development. In educational disciplines, the name of Abu Hamid Muhammad al-Ghazali or better known as Imam al-Gazhali among Muslims is a Muslim intellectual that greatly influences the thought style of Islamic thinkers from the past until now. Actually, it is impossible for the author to fully discussing al-Gazhali's views on Islamic education in this article, because of the wide range and scope of the discussion. So the article focuses on how al-Gazhali's concepts and views are related to the goals of education, curriculum, methodology, professional teachers, students and the relevance of the concepts offered by al-Gazhali with the development of education today. As writing and discussing material for this article, the author draws from sources taken from the original book by Imam al-Gazhali, further strengthened by the writings of Islamic thinkers, and supported by the results of previous research published in various national and international journals. In general, al-Ghazali's most important thinking in education is religious science with all its branches because it can be mastered through perfect reason and clear capture power. While al-Gazhali's opinion regarding the ultimate goal of education is to achieve human perfection that leads to self-approach to Allah SWT.